Impact of weather parameters on the seasonal incidence of Helopeltis antonii (Miridae: Hemiptera) on neem - Police-Patil BajiRao Chaitanya; Mallappa Bheemanna; Aralimarad Prabhuraj; Muddappa Shankara Murthy; Naik Rathod Harischandra; Dibburahalli Subbanna Aswathanarayana; Bheeranna Kariyanna (Acta Scientiarum. Biological Sciences, 2025)
Neem (Azadirachta indica A. Juss.), known for its extensive therapeutic properties, is susceptible to various pests, notably the tea mosquito bug (Helopeltis antonii Signoret). This study investigates the seasonal incidence of H. antonii on neem across different age classes and explores the correlation between meteorological factors and pest infestation. The survey monitored sixty neem trees categorized into three age groups: Category I (less than 2 years), Category II (2-6 years), and Category III (more than 6 years). Peak nymphal populations occurred in November for Categories I (12.70 nymphs/branch) and III (13.35 nymphs/branch), while Category II peaked in October (12.80 nymphs/branch). Complete drying (100% infestation) was observed from late January to mid-February for Categories I and III, and from early December to mid-February for Category II. Correlation analysis revealed a significant negative relationship between infestation levels and minimum temperature, while maximum relative humidity and sunshine hours positively correlated with pest abundance. Multi-linear regression indicated that over 90% of the variation in infestation rates could be attributed to meteorological factors. This study highlights the persistent threat of H. antonii to neem trees, regardless of age and is the first study to look at the seasonal incidence of H. antonii on different age classes of neem. Further research is required to assess the long-term implications of climate variability on H. antonii dynamics and its broader ecosystem effects.